The role of KRAS splice variants in cancer biology - Nuevo-Tapioles, Cristina; Philips, Mark R. (Frontiers in Cell and Developmental Biology, 2022)
The three mammalian RAS genes (HRAS, NRAS and KRAS) encode four proteins that play central roles in cancer biology. Among them, KRAS is mutated more frequently in human cancer than any other oncogene. The pre-mRNA of KRAS is alternatively spliced to give rise to two products, KRAS4A and KRAS4B, which differ in the membrane targeting sequences at their respective C-termini. Notably, both KRAS4A and KRAS4B are oncogenic when KRAS is constitutively activated by mutation in exon 2 or 3. Whereas KRAS4B is the most studied oncoprotein, KRAS4A is understudied and until recently considered relatively unimportant. Emerging work has confirmed expression of KRAS4A in cancer and found non-overlapping functions of the splice variants. The most clearly demonstrated of these is direct regulation of hexokinase 1 by KRAS4A, suggesting that the metabolic vulnerabilities of KRAS-mutant tumors may be determined in part by the relative expression of the splice variants. The aim of this review is to address the most relevant characteristics and differential functions of the KRAS splice variants as they relate to cancer onset and progression.